2012
DOI: 10.4028/www.scientific.net/msf.725.15
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Imaging and Wavelength Analysis of Basal Plane Frank-Type Defects in 4H-SiC Epilayers

Abstract: Abstract. Frank-type defects on a basal plane have been investigated using photoluminescence (PL) imaging microscopy and wavelength profile measurement. A wide range of emission in wavelength (>650nm) was observed from a Frank partial dislocation at the edge of the defect, while a narrow emission at around the visible light range was obtained from a stacking fault region. The emissions from a stacking fault region of three kinds of basal plane Frank-type defects were confirmed to have different wavelengths dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…A new peak appears at 424 nm in the PL spectra due to extrinsic (single extra layer) Frank-type stacking faults (SFs) in the epilayer. 31,32 During epitaxial growth, the Frank-type SFs are generally converted from a threading screw dislocation (TSD) with a Burgers vector of 1 c in the substrate. However, a micro-pit which appeared at the apex point of the TD-II was caused by a micropipe in the substrate, so the origin of the TSD in TD-II is ambiguous.…”
Section: Resultsmentioning
confidence: 99%
“…A new peak appears at 424 nm in the PL spectra due to extrinsic (single extra layer) Frank-type stacking faults (SFs) in the epilayer. 31,32 During epitaxial growth, the Frank-type SFs are generally converted from a threading screw dislocation (TSD) with a Burgers vector of 1 c in the substrate. However, a micro-pit which appeared at the apex point of the TD-II was caused by a micropipe in the substrate, so the origin of the TSD in TD-II is ambiguous.…”
Section: Resultsmentioning
confidence: 99%
“…29) In type B, the PL spectrum peak is observed at 458 nm, corresponding to the near band edge emission of 8H and SFð4; 2Þ in Zhdanov's notation. 27,28) Figure 7 shows a cross-sectional TEM image of SFs of types A and B. The cross section of these samples was chosen to be along the [11 20] direction and perpendicular to the SF base.…”
Section: Resultsmentioning
confidence: 99%
“…Then, in order to gain the evidence to prove that the leakage current point is at a triangle defect, we located the point of the leakage current inside triangular defects using a lock-in infrared camera. We performed SF characterization inside triangular defects by photoluminescence (PL) mapping and spectroscopy [26][27][28] to evaluate the SFs at a point of leakage current inside the triangular defects. Then, we identified the crystal structure of SFs by transmission electron microscopy (TEM).…”
Section: Methodsmentioning
confidence: 99%
“…Frank-type SFs are mostly formed by the 2D nucleation or by the conversion from threading screw dislocations (TSDs) during the single-crystal growth. , Various characterization methods, such as X-ray topography (XRT), photoluminescence (PL), cathodoluminescence (CL), and electroluminescence (EL), have been used to investigate the properties of SFs in 4H-SiC single crystals. Transmission electron microscopy (TEM) observations have revealed that the stacking sequences of Si–C bilayers of Shockley-type SFs include (3, 1), (6, 2), (5, 3), and (4, 4) in Zhdanov’s notation, and Frank-type SFs have the stacking sequences of (4, 1), (4, 2), and (5, 2). The local PL, CL, and EL investigations indicate that the luminescence peaks of SFs in 4H-SiC locate in the range from 420 to 500 nm. ,, The transition between a threading edge dislocation (TED) and a Shockley-type SF as well as the transition between a TSD and a Frank-type SF are also found in XRT, TEM, and EL observations. , However, these technologies mainly concentrate on the nanoscale atomic structures as well as local electronic and optical properties of a SF in 4H-SiC. Up to now, there has been limited understanding on the formation and expansion mechanisms of SFs during the PVT-growth of 4H-SiC boules.…”
Section: Introductionmentioning
confidence: 99%
“…The local PL, CL, and EL investigations indicate that the luminescence peaks of SFs in 4H-SiC locate in the range from 420 to 500 nm. 7,16,18 The transition between a threading edge dislocation (TED) and a Shockley-type SF as well as the transition between a TSD and a Frank-type SF are also found in XRT, TEM, and EL observations. 13,19 However, these technologies mainly concentrate on the nanoscale atomic structures as well as local electronic and optical properties of a SF in 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%